Characterization of a Highly Virulent Edwardsiella anguillarum Strain Isolated From Greek Aquaculture, and a Spontaneously Induced Prophage Therein - Katharios, Pantelis; Kalatzis, Panos G.; Kokkari, Constantina; Pavlidis, Michail; Wang, Qiyao (Frontiers in Microbiology, 2019)
Edwardsiella-associated outbreaks are increasingly reported on both marine and freshwater aquaculture setups, accounting for severe financial and biomass losses. E. tarda, E. ictaluri and E. hoshinae have been the traditional causative agents of edwardsiellosis in aquaculture, however, intensive studies due to the significance of the disease have just recently revealed two more species, E. piscicida and E. anguillarum. Whole genome sequencing that was conducted on the strain EA011113, isolated from farmed Diplodus puntazzo after an edwardsiellosis outbreak in Greece, confirmed it as a new clinical strain of E. anguillarum. Extensive phylogenetic analysis showed that this Greek strain is closely related to an Israeli E. piscicida-like clinical strain, isolated from diseased groupers, Epinephelus aeneus and E. marginatus in Red Sea. Bioinformatic analyses of E. anguillarum strain EA011113 unveiled a wide repertoire of potential virulence factors, the effect of which was corroborated by the mortalities that the strain induced in adult zebrafish, Danio rerio, under different levels of infection intensity (LD50 after 48 h: 1.85 x 104 cfu/fish). This strain was non-motile and according to electron microscopy lacked flagella, a fact that is not typical for E. anguillarum. Comparative genomic analysis revealed a deletion of 36 nt found in the flagellar biosynthetic gene (FlhB) that could explain that trait. Further in silico analysis revealed an intact prophage that was integrated in the bacterial genome. Following spontaneous induction, the phage was isolated, purified, characterized and independently sequenced, confirming its viability as a free, inducible virion as well. Separate genomic analysis of the prophage implies a plausible case of lysogenic conversion. Focusing on edwardsiellosis as a rapidly emerging aquaculture disease on a global scale, this work offers some insight into the virulence, fitness, and potential lysogenic conversion of a of a newly described, yet highly pathogenic, strain of E. anguillarum.